PENGARUH DOSIS BIO URINE DAN KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica Juncea L.) - I Wayan Lana; I Gede Krisna Wardana; I Gede Bagus Andika (Universitas Tabanan, 2025)
Bio Urine Dosage and Planting Media Composition and Their Interactions on the Growth and Yield of Green Mustard (Brassica Juncea L.) The study was conducted at Tabanan University campus located at Jl. Wagimin No. 8, Kediri, Tabanan, Bali. The experiment in polybags used a factorial Randomized Block Design. The treatment was the dose of Bio Urine fertilizer and the composition of the planting media, each combination treatment was repeated 3 times. The highest total fresh weight of the plant was obtained with a dose of Bio Urine fertilizer of 90 ml liter-1 of air and a composition of the planting media of soil: cow manure: burnt rice husk with a ratio of 1: 2: 1 (P3M2) which was 95.7 g and the lowest was obtained in the treatment without Bio Urine fertilizer and the composition of the planting media of soil: cow manure: burnt rice husk with a ratio of 2: 1: 1 (P0M) which was only 72.0 g or an increase in yield of 32.92%. The Single Treatment of Bio Urine fertilizer dose had a very significant effect (P <0.01) on the total dry weight of the plant oven. The highest total dry weight of the plant oven was obtained in the Bio Urine Fertilizer dose treatment (90 ml liter1 air (p2) which was 7.35 g and the lowest was obtained in the Bio Urine fertilizer treatment (P0) which was only 5.64 g or an increase of 30.32%. The single treatment of the planting media composition had a very significant effect (P<0.01) on the results of the total dry weight of the plant oven.